TOEFL Training and Professional Growth: Perceptions from Senior High School Teachers - Romios, Laser; Daffa Arief Rajendra (Universitas PGRI Yogyakarta, 2025)
This study explores senior high school teachers’ perceptions of TOEFL training as part of their professional development. While English proficiency—often measured by standardized tests like the TOEFL—is increasingly important in academic and career advancement, little research has examined how in-service secondary school teachers view its relevance. Using a qualitative descriptive method, data were collected through interviews with four teachers who had participated in a short TOEFL training program. The findings reveal mixed perceptions: while many teachers acknowledged the value of the training and expressed a strong interest in improving their English skills, institutional support was often lacking, and training was viewed as optional rather than a coordinated effort. Additionally, participants identified time constraints, test anxiety, and a preference for more in-depth language development as key challenges. The study concludes that although teachers recognize the importance of TOEFL for global mobility and academic credibility, sustainable professional development requires systemic support, differentiated training design, and clearer career incentives.